Response of digestive organs of Hypsiboas albopunctatus (Anura: Hylidae) to benzo[α]pyrene - Fanali, Lara Zácari [UNESP]; De Lacerda Valverde, Bruno Serra [UNESP]; Franco-Belussi, Lilian [UNESP]; Provete, Diogo B.; De Oliveira, Classius [UNESP] (De Gruyter, 2017)
Anurans are exposed to several pollutants. One of these is benzo[α]pyrene (BaP). This compound is produced by incomplete combustion and is toxic to the liver and intestine, where it is metabolized. Here, we tested how different concentrations of BaP affect the thickness of small intestine and liver melanomacrophages (MMCs) of Hypsiboas albopunctatus during short-and long-term exposures. We conducted an experiment with a 3 × 2 factorial design to answer these two questions. Male specimens were separated into groups injected with either 3 or 7 mg/kg of BaP and euthanized after either 72 or 168 h. Then, we measured the thickness of the intestinal epithelium and the area occupied by MMCs. The thickness of intestinal epithelium decreased in both high and low concentration for short-term exposure compared to control, and increased in the long-term group in both low and high concentrations. The short-term decrease in thickness is due to the damage caused by BaP on the absorptive capacity of the epithelium, whereas the epithelium increased its thickness and recovered normal activity in the long-term. High BaP concentration decreased the area of MMCs in the short-term group. The increase in MMCs is associated with the detoxifying role of these cells, while the decrease was triggered by cellular stress due to high BaP concentration. The concentrations of BaP we used are close to those found in polluted environments. Therefore, water contaminated with BaP can potentially affect the morphology of internal organs of anurans.
Keywords: benzo[Α]pyrene; digestive system; intestinal epithelium; melanin; melanomacrophage